Sociodemographic determinants of multidrug-resistant tuberculosis in Lesotho: A case-control study. - Jerry Yakubu Yahaya (PLOS Global Public Health, 2025)
The emergence of multidrug-resistant tuberculosis (MDR-TB) significantly undermines global efforts toward tuberculosis (TB) control, particularly in high-burden settings like Lesotho. Understanding the sociodemographic factors contributing to MDR-TB is crucial yet remains under-explored in this context. This study aimed to identify key sociodemographic determinants associated with MDR-TB among adult TB patients in Lesotho. Using a retrospective case-control design, I analyzed data from 306 participants, including confirmed MDR-TB cases and drug-susceptible TB controls, recruited from 12 TB clinics between March 2021 and February 2022. Sociodemographic characteristics (age, sex, education, employment, income, place of residence), HIV status, and caregiver presence were examined using chi-square tests and multivariable logistic regression analyses. The findings indicated that individuals older than 26 years had lower odds of MDR-TB compared to those aged 18-26 years (OR = 0.8, 95% CI 0.67-0.99, p = 0.040). Similarly, higher income levels (earning more than $1,026 annually) were associated with reduced odds of MDR-TB (OR = 0.5, 95% CI 0.22-0.94, p = 0.034). Conversely, the absence of caregiver support significantly increased the likelihood of MDR-TB by 80% (OR = 1.8, 95% CI 1.04-3.11, p = 0.036). These findings highlight the critical need for targeted interventions focusing on socioeconomic empowerment, caregiver support, and tailored public health education to effectively mitigate the MDR-TB burden in Lesotho.